The potencial influence of rice husk ash in self compacting mortar: Cases of mechanical strength and water absorption - Alcantara, Marco Antônio de Morais [UNESP]; de Mello, Anna Beatriz Alves [UNESP]; de Albuquerque, Maria da Consolação Fonseca [UNESP] (FapUNIFESP (SciELO), 2018)
The study presents an experiment on the use of rice husk ash (R.H.A) for the production of self-compacting mortars. For this purpose, CPZ II 32 cement, natural sand, industrialized rice hull ash, electrostatic and steric performance superplasticizer, and water were used. Two types of mortars were produced, one series to be densi-fied with the aid of vibration, and another series with the incorporation of R.H.A in the 35% content in relation to the mass value of the cement, and of superplasticizer, to be made strong by the action of its own weight. The values of water/cement ratio were 0.4, 0.5 and 0.6 for cases of vibrated mortars and 0.68, 0.63 and 0.55 for cases of self-compacting mortars. For the vibrated mortars were performed in the fresh state the consistency tests with aid of the table of blows, slump tests, and the evaluation of the apparent specific mass. For the self-compacting mortars, the slump flow tests were carried out in the fresh state and the flow test confined with the aid of the funnel; besides the evaluation of the apparent specific mass. In the hardened state the tests of compressive strength and diametrical compressive strength, and of water absorption were realized at 7, 28, 60 and 90 days of cure. It was observed that the mortars with the addition of R.H.A and the vibrated ones presented mobility conditions compatible with respect to each case and absence of segregation; The mortars with R.H.A presented mechanical strength values slightly higher than those presented by vibrated mortars, as well as lower absorption values, despite the higher values for the water / cement ratio compared to the cases of vibrated mortar.
A influência potencial das cinzas de casca de arroz em argamassas auto adensáveis: Casos da resistência mecânica e da absorção d’água
Keywords: Absorption; Mechanical properties; Rice husk ash; Self-compacting mortars